2023
DOI: 10.34133/research.0084
|View full text |Cite
|
Sign up to set email alerts
|

Organic Passivation of Deep Defects in Cu(In,Ga)Se 2 Film for Geometry-Simplified Compound Solar Cells

Abstract: Diverse defects in copper indium gallium diselenide solar cells cause nonradiative recombination losses and impair device performance. Here, an organic passivation scheme for surface and grain boundary defects is reported, which employs an organic passivation agent to infiltrate the copper indium gallium diselenide thin films. A transparent conductive passivating (TCP) film is then developed by incorporating metal nanowires into the organic polymer and used in solar cells. The TCP films have a transmittance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…61 Recombination active defect states at interfaces and in the bulk of CuIn 1− x Ga x Se 2 solar cells restrict the open-circuit voltage and fill factor. 62…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Recombination active defect states at interfaces and in the bulk of CuIn 1− x Ga x Se 2 solar cells restrict the open-circuit voltage and fill factor. 62…”
Section: Resultsmentioning
confidence: 99%
“…61 Recombination active defect states at interfaces and in the bulk of CuIn 1Àx Ga x Se 2 solar cells restrict the open-circuit voltage and fill factor. 62 For survived La 3 CoCrS 7 , Y 3 CoCrS 7 and Y 3 TiCuS 7 , we further calculated the effect of point defects on the electronic structure. All possible intrinsic point defects include seven types of vacancies (V La,Y , V Co,Cr,Ti,Cu , V S ).…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Defects, including various atom vacancies and various dangling bands of nanocrystals, are common in materials that could trap carriers [62][63][64]. These defects contribute to carrier trapping and regulation of the conductivity in synaptic transistors.…”
Section: Capture and Release Of Carriersmentioning
confidence: 99%
“…Therefore, by controling doping, you control the density of bulk defects or you control the quantity of acceptors, charge carrier mobility and lifetimes [12] available which affect photo cell performance. Doping has been linked to the presence of intrinsic defects [6,9,17,46] in thin films and one study revealed that an excess of selenium introduces a n-type [46] conductivity while a deficiency of selenium lead to p-type [41]. Therefore, acceptor density is a key parameter to consider in addition to bulk defect density.…”
Section: Influence Bulk Defect Density On Thicknessmentioning
confidence: 99%
“…For purposes of testing, two different ohmic contacts made out of either molybodium or an alloy of nickelaluminium (Ni/Al) [4] are used to collect any photo-generated electrons and holes upon illumination. Recent studies [5,6,7] have successfully investigated many opto-electrical parameters of CIGS photocells but few have concentrated on the influence of bulk defect density on their performance.…”
Section: Introductionmentioning
confidence: 99%